2022
DOI: 10.1017/s0954579421001590
|View full text |Cite
|
Sign up to set email alerts
|

More than a feeling? An expanded investigation of emotional responsiveness in young children with conduct problems and callous-unemotional traits

Abstract: Children with conduct problems and high callous-unemotional (CP+CU) traits are characterized by dampened emotional responding, limiting their ability for affective empathy and impacting the development of prosocial behaviors. However, research documenting this dampening in young children is sparse and findings vary, with attachment-related stimuli hypothesized to ameliorate deficits in emotional responding. Here we test emotional responsiveness across various emotion-eliciting stimuli using multiple measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 102 publications
0
2
0
2
Order By: Relevance
“…This result might be accounted for by several reasons. At first, Northam et al sampled 2–8 years old children and found that children with a high level of CU traits display deficits in many aspects of emotional responses [ 25 ]. Emotional responses promote the development of prosocial behavior and empathy, and help children identify and perceive negative emotions in their peers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result might be accounted for by several reasons. At first, Northam et al sampled 2–8 years old children and found that children with a high level of CU traits display deficits in many aspects of emotional responses [ 25 ]. Emotional responses promote the development of prosocial behavior and empathy, and help children identify and perceive negative emotions in their peers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a longitudinal study by Waller et al indicated that children’s CU traits at age three predicted their high levels of aggression and peer exclusion at age ten [ 24 ]. Children with CU traits already exhibit emotional recognition difficulties, moral-emotional deficits, and fearlessness in childhood [ 23 , 25 , 26 ]. However, these features are often associated with less prosocial behavior and more externalizing behavioral problems in young children [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.18413/231366-78. DOI: 10.18413/ -8971-2022 (Northam, et al, 2022); недостаток эмоциональной отзывчивости может привести к хроническому и стойкому антисоциальному поведению Raine, et al, 2014). Важно, что и в зарубежных исследованиях внимание ученых обращено, в основном, к детям дошкольного возраста: дети с проблемами в социальном развитии и с проблемами в поведении характеризуются отсутствием эмпатии, угрызений совести, явным пренебрежением правами других, что нередко является основной причиной антисоциального поведения впоследствии ; дети с диагностируемыми показателями черствости и неэмоциональности (CP + CU) демонстрируют выраженные агрессивность, эмоциональный дефицит, в том числе -сниженную эмоциональную отзывчивость на сигналы бедствия других людей (Kimonis, et al, 2019).…”
unclassified
“…Учитывая потенциальное значение эмоциональной отзывчивости для этиологии антисоциального поведения, в зарубежных публикациях делается акцент и на процедурах эмпирического изу-чения, поскольку «процесс регистрации эмоциональных состояний других людей и реагирования на них служит основой для развития просоциальных убеждений и моделей поведения» (Schwenck, et al, 2017). При этом, в диагностических процедурах наряжу с физиологическими показателями особое внимание уделяется поведенческому критерию эмоциональной отзывчивости (Northam, et al, 2022).…”
unclassified